Embebição de sementes de soja para o teste de germinação - Palagi, Celso Ari (2004)
The culture of the Soya has great economic importance in the Brazilian agricultural scenery, from being that the production of seeds significantly to contribute importance with this process. Methods and tests of quality estimate of the seeds really have been showing their potential are avail large so, this work had purpose to seek a alternative methodology capable of to minimize the harm soak up during the realization the tests of the seeds germination standard. For so much, seeds coming from three places of production from South Brazil area, harvested the agricultural bearing 2001/02, of the cultivars CD 201, CD 202 and CD 210 were rated via middle of the tests: first couting of germination, tests germination standard of, percentile of plantule abnormal, tetrazolium germination, tetrazolium worth and emergency on soil flooring. The tests were done on two ages; the first on three months after harvest and the second on six months after harvest. On all tests parts of the seeds were pre-soaking prior of the realization of the same, the other party did follow the traditional methodology. The pre-soaking constituted in the setting of the seeds on ductile boxes (gerbox). On the screen steely inox containing 40 fl Oz milligram water, during a period of 24h the 25ºC, on camera of germination of type Mangelsdorf. After this period the seeds were analyzed in the diverse tests, according the prescribed in the Rules Parsing of Seeds. The sowing in the soil, for the evaluation of the emergency, went executing on hothouse covered with transparent sailcloth ductile like a tunnel. The contour experimental utilized was casually with four iterations. The Work were unfolded on two experiments conform origin the seeds; in the first went compared with the cultivars CD 201 and CD 202 and in the second analyzed only the CD 210. The results were, then, submitted to statistical parsing firstly, individually within on each epoch of evaluation on each place, and subsequent to proceeded the parsing conjoint considering two ages and the three places. The procured results permit to make conclusion that the results pre-soaking introduced 6% TPG seeds, only to the cultivar CD 202. To the three places, if nothing else one of the ages of realization tests. The responses positive of the pre-soaking of the seeds of cultivar CD 202 is compatible with the procured results in the test of tetrazolium/viability (1-5) e of emergency on soil.